Anthropology of sexual exploitation - Lalić Velibor; Kešetović Želimir (Temida)
In this paper, the authors observe sexual exploitation from an anthropological perspective. They analyze the rational, ethical, emotional and mythological dimensions of human sexuality. Consequently, after setting the phenomenon in a social and historical context, sexual exploitation is closely observed in the contemporary age. Based on thoughts of relevant thinkers, they make the conclusion that the elimination of sexual exploitation is not an utterly legal issue, but political and economical issues as well. Namely, legal norms are not sufficient to overcome sexual exploitation, but, political and economical relationships in contemporary societies, which will be based on sincere equal opportunities must be established.